Evaluation of interpolation methods of bathymetric data at the Poxim-Açu river dam – SE (Research, Society and Development, 2020)
The depth of natural water reservoirs is usually estimated through bathymetry spot data. Once bathymetric data are collected, data values are spatially distributed using interpolation methods. This study aimed to evaluate the performance of three different types of interpolators across a range of bathymetric data collected at the Poxim river dam, in the state of Sergipe. In September 2016, 882 bathymetric measurements were performed in the water reservoir. The bathymetric data were spatialized using three methods: inverse distance square interpolation, spline and kriging. The resulting estimates were evaluated and the best method was chosen based on cross-validation statistics (RMSE). The Poxim river dam presents an average depth of approximately 8.6 m, with maximum and minimum values of 19.3 and 0.5 m, respectively. Kriging was pointed out as the best interpolation model, along with the spherical semivariogram adjustment, with RMSE values of 1.64 m in cross-validation, followed by the inverse distance square (RMSE = 1,69 m) and spline (RMSE = 1,72 m). Therefore, kriging is the recommended model for the spatialization of bathymetric data in the evaluated water reservoir.